Influence of Vaccine Drive Thru Service Qualityon Perceived Value and Customer Satisfaction - Berliana, Nandhita Evieta; Munawaroh , Munjiati (Universitas Muhammadiyah Yogyakarta, 2023)
This type of research is research that uses a quantitative approach. By using this approach, significant results will be obtained for the variables to be examined by formulating a hypothesis to determine whether it is accepted or rejected. This research is intended to test the influence of vaccine drive thru service quality on perceived value and customer satisfaction. The purpose of this study is to analyze the influence of the quality of the physical environment, the quality of online registration, and the quality-of-service officers on perceived value and its consequences on customer satisfaction. The subjects in this study were drive thru vaccine participants at Muhammadiyah University of Yogyakarta. In this study, a sample of 200 respondents and the analysis tool used is the Structural Equation Model (SEM) through the AMOS program version 26. This study failed to prove the influence of the quality of the physical environment on customer perceived value in the Covid-19 vaccination drive thru service. This cannot be generalized to other types of services. Therefore, future research can examine types of services other than drive through so that they can be generalized to other types of services.